Contribution of Glycosaminoglycans to the Microstructural Integrity of Fibrillar and Fiber Crimps in Tendons and Ligaments. (2010) - Franchi, Marco; De Pasquale, Viviana; Martini, Désirée; Quaranta, Marilisa; Macciocca, Maria; Dionisi, Alessio; Ottani, Vittoria
Abstract : The biomechanical roles of both tendons and ligaments are fulfilled by the extracellular matrix of these tissues. In particular, tension is mainly transmitted and resisted by protein (collagen, elastin) fibers, whereas compression is opposed by water-soluble glycosaminoglycans (GAGs). GAGs spanning the interfibrillar spaces and interacting with fibrils through the interfibrillar proteoglycans also seem to play a part in transmitting and resisting tensile stresses. Both tendons and ligaments showing similar composition, but different functional roles and collagen array, exhibit periodic undulations of collagen fibers or crimps. Each crimp is composed of many knots of each single fibril or fibrillar crimps. Fibrillar and fiber crimps play a mechanical role in absorbing the initial loading during elongation of both tendons and ligaments, and in recoiling fibrils and fibers when tissues have to return to their original length. This study investigated whether GAGs covalently attached to proteoglycan core proteins directly affect the 3D microstructural integrity of fibrillar crimp regions and fiber crimps in both tendons and ligaments. Achilles tendons and medial collateral ligaments of the knee from eight female Sprague-Dawley rats (90 days old) incubated in a chondroitinase ABC solution to remove GAGs were observed under a scanning electron microscope (SEM). In addition, isolated fibrils of these tissues obtained by mechanical disruption were analyzed by a transmission electron microscope (TEM). Both Achilles tendons and medial collateral ligaments of the rats after chemical or mechanical removal of GAGs still showed crimps and fibrillar crimps comparable to tissues with a normal GAG content. All fibrils in the fibrillar crimp region always twisted leftwards, thus changing their running plane, and then sharply bent, changing their course on a new plane. These data suggest that GAGs do not affect structural integrity or fibrillar crimp functions that seem mainly related to the local fibril leftward twisting and the alternating handedness of collagen from a molecular to a supramolecular level.